2019
DOI: 10.1111/ctr.13760
|View full text |Cite
|
Sign up to set email alerts
|

Patient survival following renal transplantation in Indigenous populations: A systematic review

Abstract: Background: Inequities in health care predispose Indigenous populations to poor health outcomes. The objective of this study was to examine patient survival and other post-transplant outcomes of kidney transplantation among Indigenous patients compared with non-Indigenous populations. Methods: A systematic review of MEDLINE, EMBASE, and Google Scholar was undertaken from inception to September 30, 2019, using a computerized search. Publication descriptors and methodological and statistical details were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…When we examined graft survival, we found that Aboriginal and Torres Strait Islander children and young adults graft survival was similar to that for non‐Indigenous children and young adults at five years but was lower at ten years. Similar findings were reported for First Nations adults in Australia 18 and overseas 19 . Longer cold ischaemia time (particularly longer than 18 hours) was more frequent among Aboriginal and Torres Strait Islander than non‐Indigenous kidney transplant recipients in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…When we examined graft survival, we found that Aboriginal and Torres Strait Islander children and young adults graft survival was similar to that for non‐Indigenous children and young adults at five years but was lower at ten years. Similar findings were reported for First Nations adults in Australia 18 and overseas 19 . Longer cold ischaemia time (particularly longer than 18 hours) was more frequent among Aboriginal and Torres Strait Islander than non‐Indigenous kidney transplant recipients in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported for First Nations adults in Australia 18 and overseas. 19 Longer cold ischaemia time (particularly longer than 18 hours) was more frequent among Aboriginal and Torres Strait Islander than non-Indigenous kidney transplant recipients in our study.…”
Section: Graft Survivalmentioning
confidence: 42%
See 2 more Smart Citations